Robotic Knitting Re-Crafting Human-Robot Collaboration Through Careful Coboting - Treusch, Pat (Science Studies, 2020)
As a reaction to typically dead-end debates on future human and robot collaboration that tend to be either dismissive or overly welcoming towards »cobot« technologies, this book provides a technofeminist intervention. Pat Treusch not only shows how both the fields of technofeminism and robotics can engage in a practical exchange through knitting, but also contributes a tangible example of coboting dynamics. Robotic Knitting re-negotiates the boundaries between formalisation and embodiment, craft and high-tech as well as useful and dysfunctional machines. It re-crafts the nature of collaboration between human and robot. This finally entails an alternative mode of relating - a mode that enables an account of careful coboting.